Economic Effects of the Black Death: Spain in European Perspective - Carlos Álvarez-Nogal; Leandro Prados de la Escosura; Carlos Santiago-Caballero (European Historical Economics Society (EHES), 2020)
The Black Death was the most devastating demographic shock in recorded human history. However, the effects in the European population were highly asymmetrical as were its economic consequences. This paper surveys the short and long run economic effects of the plague in Spain in European perspective. While the demographic impact in Spain was moderate compared to the European average, the economic effects were more severe and incomes per head fell sharply. This was a consequence of the existence of a frontier economy in Spain characterised by a relative scarcity of labour and a fragile equilibrium between factors of production. Unlike most of Europe, in Spain the Black Death increased inequality as the remuneration of labour decreased more rapidly than proprietors' gains. In the long term the Plague reinforced the frontier economy status.
Keywords: I10; N13; N33; O52; 330; Black Death; Frontier economy; Malthusian; Spain; income; inequality